(untitled) (International Journal of Technology and Management Research, 2020)
This paper examines how cash resources affect the sustainable environmental practices and financial performance of firms listed on the Alternative Investment Market (AIM) in the United Kingdom (UK). The study adopts Ordinary Least Square (OLS) regression model on 201 quoted Small and Medium Enterprises (SMEs) on the UK Alternative Investment Market (AIM) from 2011 to 2016. Consistent with our predictions and confirms with the assertions of the resource-based view, the study documents that cash resources have a positive impact on sustainable environmental practices and financial performance relationships. However, the direction of the regression coefficient was not the same for accounting (ROA) and market-based (Tobin’s q) measures of financial performance. Whereas the moderating impact between cash resources and sustainable environmental practices for ROA was negative, the relationship was positive in the case of Tobin’s q. The study, therefore, concluded that where excessive cash are employed in the management and implementation of environmental sustainability, the financial returns may not be favourable. However, efficient utilisation of cash resources may positively impact on sustainable environmental practices and financial performance relationships. The study also documented that unconstraint firms have a higher probability of benefiting financially from environmental sustainability measures than cash constraint firms. Citation: Danquah Jeff Boakye1, Gabriel Sam Ahinful2 and Randolph Nsor-Ambala3. Sustainable Environmental Practices and Financial Performance Relationships. Are they moderated by Cash Resources? Evidence from Alternative Investment Market in the United Kingdom., 2020; 5(1): 14－29. Received: (February 15, 2020) Accepted: (March 31, 2020)